PTH-049 Clinical outcomes of endoscopic submucosal dissectionfor colorectal neoplasms: a single UK referral centre experience. (8th June 2018) - Papastergiou, Vasilios; Stasinos, Ioannis; Rameshshanker, Rajaratnam; Wawszczak, Aurelia; Man, Ripple; Polecina, Adel; Warusavitarne, Janindra; Tsiamoulos, Zacharias; Suzuki, Noriko; Saunders, Brian
Abstract : Introduction: There is limited experience of endoscopic submucosal dissection (ESD) for resection of colorectal lesions in the West and outcome data tends to be worse than that reported from Japanese centres. We report the outcomes of ESD in a single, tertiary UK referral centre. Methods: A prospective database was analysed including 165 consecutive patients (mean age: 64.6±12.6 years, 62.4% males) with 173 colorectal neoplasms resected by ESD between 3/2012 and 12/2017. Two experienced colonoscopists performed all procedures. Results: The median (IQR) lesion size was 3.5 cm (2–5), and 140 (80.9%) were located in the rectum. Overall, 49.7% were granular-type laterally spreading tumours (LST), 19.7% were non-granular LST, and 30.6% were polypoid lesions. In 29 (16.7%) cases a flexible endosurgical platform was used to assist ESD of complex rectal polyps [median(IQR) size: 6 cm (5–8)] by dynamic trans-anal retraction (Trans-Anal Submucosal Endoscopic Resection; TASER). Histology showed low-grade adenoma/dysplasia in 83 (47.9%), high-grade adenoma/dysplasia in 52 (30%), T1 cancer (<1000 µm) in 17 (9.8%), and T1 cancer (<1000 µm) in 17 (9.8%) lesions. The en bloc, histological complete and curative (R0) resection rates were 97.7%, 80.3% and 76.3% respectively. Three (1.7%) cases of delayed bleeding occurred, with one case requiring transfusion. Perforation occurred in 2 (1.2%) cases: one was recognised and treated intraoperatively with endoclips; the other one was followed up and managed conservatively. Sixty (34.7%) patients were electively admitted to hospital post procedure, for a median duration of 1 day (range 1–5). Twenty patients (12.1%), at risk of lymph node metastasis, underwent additional radical surgery. Eighty-nine (51.4%) ESD cases had endoscopic follow-up data over a median duration of 12 months (range 3.4–51.3). The local recurrence rate was 4/89 (4.5%); all recurrent cases were managed endoscopically. The recurrence rate was lower in cases with en bloc compared with piecemeal resection (3.4% vs 50%, p=0.08), histologic complete compared with histologic incomplete resection (2.5% vs 22.2%, p=0.05), and R0 compared with non-R0 resection (2.5% vs 20%, p=0.06). After a median follow up of 14.6 months (range: 3–55.8), the overall and disease-specific survival in the study population was 98.8% and 100%, respectively. Conclusions: The current study demonstrates favourable clinical outcomes of selected colorectal ESD in a Western endoscopy setting. Further studies addressing the cost-effectiveness of ESD and comparing its long-term outcome with endoscopic mucosal resection in the West are needed.